The Evolution of an Academic Library Community Through Its Strategic Choices - Moul, Richard H. (Journal of library administration, 2024)
This article reviews the evolution of PASCAL, a statewide academic library consortium in South Carolina, with a focus on how factors such as the priorities of member libraries, a focus on building "mutually reinforcing" programming, and the availability of funding have impacted its evolution. Borrowing from Brian Lavoie's model of library decision-making regarding sourcing options, it seeks to illustrate that the decisions libraries make regarding how they interact with consortia intersect with the decisions made by a consortium itself, and further that-at least in the case of PASCAL-these choices have been made interactively.